The Effect of Service Quality and Price Perception on Patient Loyalty Mediated by Patient Satisfaction - Fathillah, Muhammad Ichsan (International Journal of Social Service and Research, 2023)
This study aims to see the effect of service quality and price perception on patient loyalty which is mediated by patient satisfaction. Respondents in this study were patients who came to the PUSPIPTEK Medical Center. Hypothesis testing was carried out using quantitative research with a sample size of 100 respondents. Data were obtained through electronic questionnaires that were digitally administered to respondents. The analysis technique used is Partial Least Square - Structural Equation Modeling (PLS-SEM) using the SmartPLS program. Based on the results of data processing and data analysis it was found that there is a significant effect of service quality on patient satisfaction, there is an effect of Price Perception on patient satisfaction, there is no effect of service quality on patient loyalty, there is a significant effect of price perception on patient loyalty, indirectly there is the effect of service quality on patient loyalty mediated by patient satisfaction, and indirectly there is a significant effect of price perception on patient loyalty by mediating patient satisfaction. The PUSPIPTEK medical center is one of the existing ones in the South Tangerang area. With this, the management can update other health service measures, such as the practice of specialist doctors along with increasing consumer desires and increasing consumer needs.